SUPPORT FOR AGRICULTURE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Norbert R Mingueyambaye, Chad: 'I must respond having read Mr Miri Setoe's Viewpoint in Spore No. 66. There is no doubt that all aspects of agriculture should be supported, especially when you consider that it is through agriculture that we get most...